Educating smokers about the risk of blindness – insights to improve tobacco product health warning labels. Issue 1 (December 2016) - Kennedy, Ryan; Hammond, David; Spafford, Marlee; Douglas, Ornell; Brûlé, Julie; Fong, Geoffrey; Schultz, Annette
Abstract Background Health warning labels (HWL) on tobacco products help educate smokers about the health effects from smoking; however, there is a need to improve HWL content including images and text to increase effectiveness. In Canada, a HWL was created that communicates smoking's causal association with "blindness" from age-related macular degeneration (AMD). This study surveyed Canadian optometrists about their opinions regarding the image and text used in the "blindness" HWL. Methods An online survey was sent to all 4528 registered Canadian optometrists. Respondents were asked if the HWL conveyed important and believable information, and if the picture was appropriate. Optometrists were invited to make open-ended comments about the label which were analyzed using a qualitative analysis framework suitable for health policy evaluation. Frequency distributions were calculated for closed-ended questions. Results The survey was completed by 850 respondents (19 %). Most respondents (90 %) reported the message was believable/somewhat believable; while 35 % felt the picture was "too graphic". Some respondents reported in their open-ended comments that they were concerned the HWL was internally inconsistent because it reports there is "no effective treatment in most cases" for AMD but the image depicts someone undergoing surgery. There was concern that this may discourage patients from seeking needed treatment. Conclusion The majority of Canadian optometrist respondents were in agreement that the new, "RISK OF BLINDNESS" pictorial HWL includes important, believable information. Some optometrists had concerns that the HWL included a confusing message or a message that may discourage some patients from pursuing treatment for AMD. Future development of blindness-related HWL should seek practitioner input.